Perancangan Sistem Pakar Bersbasis Web untuk Mendiagnosis dan Menangani Penyakit Pada Tanaman Pala - Idhar Adjam; Fitriyanti Faruk; Farid Madjodjo; Indra Altarans (Jurnal Ilmiah Wahana Pendidikan, 2022)
Artificial intelligence is a part of computer science that is widely used because of its ability to imitate human thinking. Computers have penetrated into various fields of life And expert systems are a branch of artificial intelligence that studies how to adopt the way of thinking of an expert in solving a problem, and make a decision or draw conclusions from a number of facts. In this case the expert system is used to diagnose diseases in Nutmeg plants using the Forward chaining method. With the aim of being able to assist in diagnosing diseases in Nutmeg plants and getting precise and accurate diagnostic results. This final project will discuss a web-based expert system for diagnosing and treating diseases in nutmeg. The method used is forward chaining with forward tracking, with an easy design and in accordance with existing rules. The program created is expected to represent an expert in diagnosing diseases. The expert system created is used as a tool for someone to find solutions to problems in nutmeg plant diseases.